Information Technology and Religiosity as Moderating Variables of the Relationship between Investment Risk-Taking and Firm Performance - Wida Purwidianti; Ika Yustina Rahmawati; Lahan Adi Purwanto (University of Merdeka Malang, 2022)
Study on the impact of investment risk-taking on the performance of small and medium enterprises (SMEs) are still inconsistent. This study provides novelty to the relationship between the two variables by adding moderating variables of information technology and religiosity. This study took a sample of 94 SME owners in Banyumas Regency. The results show that the influence of investment risk-taking and information technology has no significant results. The higher level of religiosity of the SME owners will be able to improve the company's performance. The moderating relationship between information technology and investment risk-taking shows significantly positive results. In contrast, the moderating effect of the religiosity variable will further reduce the effect of investment risk-taking on company performance.